Estudo da formação de biofilmes bacterianos em endopróteses (“stent”) e inibição da formação de biofilme por peptídeos antimicrobianos de venenos de artrópodes - Neves, Rogério Coutinho das (2019)
The use of synthetic materials as temporary or permanent insertion in the body can result in infections associated with the colonization of these materials. The colonization of these materials can result in bacterial biofilms formation. Acinetobacter baumannii infections are difficult to treat due to biofilm formation and resistance to multiple drugs. Staphylococcus strains are able to form biofilm and to resist against antibiotics, in addition of being associated with endocarditis. Thus, in this thesis we hypothesize that hospital acquired bacteria were able to form biofilm in vascular stent. In this study, the biofilm formation in polystyrene plates and on coronary stents of three isolates of multidrug-resistant A. baumannii (MDR) AB 02, AB 53 and AB 72 were evaluated. The biofilm formation in coronary stents were analyzed by scanning electron microscopy. The antimicrobial peptides from wasps (Agelaia-MPI, Polydia-MPII, Polydim-I) and scorpion (Con10 and NDBP 5.8) were used to determine the minimum inhibitory concentration (MIC) and biofilm eradication (MBEC) of A. baumannii on polystyrene plates. Additionally, methicillin resistant Staphylococcus spp was also used to evaluate the ability of peptides to inhibit biofilm formation. A. baumannii MDR in contact with the vascular stent adhered to the biomaterial and initiated the formation of bacterial biofilm. The MIC of the wasp peptides against strains of A. baumannii MDR ranged from 3.12 to 6.25 μM and those of scorpion from 6.25 to 25 μM. The MBEC of Agelaia-MPI and Polybia-MPII was 6.25 μM. Con10 presented a 6.25 μM MBEC for the AB 72 strain and 12.5 μM for the AB 02 and AB 53 strains and the NBDP 5.8 inhibited at the 25 μM concentration. Agelaia-MPI inhibited the biofilm dispersion of AB 02 and AB 53 at 6.25 μM concentration and of AB 72 at 12.5 μM. Polybia-MPII inhibited at the concentration 6.25 μM. Agelaia-MPI and Polybia-MPII inhibited mature biofilms at 6.25 μM. Because Agelaia and Polybia peptides presented the best inhibitory performance they were tested against Staphylococcus ssp. Polybia-MPII and Agelaia-MPI showed MIC and MBEC of 12.5 μM. We conclude that A. baumannii forms biofilm in both plates and on vascular stents. The AMPs from wasp venoms (Agelaia-MPI and Polydia-MPII) prevent the biofilm formation of both A. baumannii and Staphylococcus epidermidis. These peptides were also able to reduce the bacterial load of biofilm-containing biomaterials. Therefore, we suggest that the Agelaia-MPI and Polybia-MPII antimicrobial peptides may be modified to coat biomaterials and prevent biofilm formation as well as for the treatment of individuals afflicted with contaminated biomaterials.